Effects of xanthan, guar, carrageenan and locust bean gum addition on physical, chemical and sensory properties of meatballs - Demirci, Zeynep Ozben (Springer India, 2011)
This study evaluated the effects of xanthan gum, guar gum, carrageenan and locust bean gum on physical, chemical and sensory properties of meatballs. Meatball samples were produced with three different formulations including of 0.5, 1, and 1.5% each gum addition and gum added samples were compared with the control meatballs. Physical and chemical analyses were carried out on raw and cooked samples separately. Moisture contents of raw samples decreased by addition of gums. There were significant decreases (p < 0.05) in moisture and fat contents of raw and cooked meatball samples formulated with gum when compared with control. Ash contents and texture values increased with gum addition to meatballs. Meatball redness decreased with more gum addition in raw and cooked meatball samples, which means that addition of gums resulted in a lighter-coloured product. According to sensory analysis results, locust bean gum added (1%) samples were much preferred by the panelists.